Analysis of Financial Ratio Determinants for Increasing Operating Profit in MSMEs Service Sector: an Empirical Case Study from Barber Shop Business in Indonesia - Muammar Khadafi; Marzuki Marzuki; Chairil Akhyar; Chalirafi Chalirafi; Fuadi Fuadi; Irada Sinta; Rico Nur Ilham (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
This study aims to analyze the Financial Ratios of MSMEs in the haircut service sector at Raden The Barber Banda Aceh from 2015-2019. The data analysis method used in this study uses Profitability Ratios, Liquidity Ratios, Solvency Ratios and Activity Ratios to assess Financial Performance, in accordance with the regulations stipulated by the Decree of the Minister of Small and Medium Enterprises of the Republic of Indonesia No. 06/Per/M.KUKM/V/2006. From the results of data analysis, it can be seen that the Profitability Ratio of Raden The Barber Banda Aceh from 2015-2019 can be said to be good, with indicators of GPM (99.35%), NPM (56.78%) and ROA (18.26%), with an overall indicator has a value greater than 10%. The results of the analysis of the Liquidity Ratio of Raden The Barber Banda Aceh from 2015-2019 can be said to be good, with the QR (622.97%) and CR (695.41%) indicators with overall indicators having values greater than 200%. Furthermore, the results of the Solvency Ratio analysis of Raden The Barber Banda Aceh from 2015-2019 can be said to be good, with the DAR indicator (1.45%) which has a value less than 40%. Finally, the results of the analysis of Raden The Barber Banda Aceh's Activity Ratio from 2015-2019 can be said to be good, with indicators of TATO (32.11%) and RTO (15.13%), with overall indicators having values greater than 10%.